2020
DOI: 10.1007/s00415-020-09916-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental factors and physical activity on disability and quality of life in CIDP

Abstract: A few observational studies and randomized trials suggest that exercise and rehabilitation may improve activity limitation and quality of life (QoL) in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), but the impact of other modifiable factors on the severity of the disease is not well understood. Using a structured questionnaire, we collected data on lifestyle and dietary habits of the patients included in the Italian CIDP database to investigate the possible influence of modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…In real life the influence of these factors is under discussion. In a study with 323 CIDP patients physical activity improves symptom severity, disability and quality of life, but other environmental factors as smoking, alcohol and different dietary regimes did not have an impact on the severity and health perception of CIDP [98].…”
Section: The Challenge Of Understanding Aetiology Of Cidp Nutrition Amentioning
confidence: 88%
See 1 more Smart Citation
“…In real life the influence of these factors is under discussion. In a study with 323 CIDP patients physical activity improves symptom severity, disability and quality of life, but other environmental factors as smoking, alcohol and different dietary regimes did not have an impact on the severity and health perception of CIDP [98].…”
Section: The Challenge Of Understanding Aetiology Of Cidp Nutrition Amentioning
confidence: 88%
“…The data on the influence of nutrition and environmental factors in CIDP are scarce. Several studies have shown an association of diet and environmental factors like tobacco and alcohol consumption with the progression of disability in different autoimmune diseases [98,99]. In neuroinflammatory and neurodegenerative diseases, the immunological influence of the gut microbiome has increasingly gotten into focus of research [100].…”
Section: The Challenge Of Understanding Aetiology Of Cidp Nutrition Amentioning
confidence: 99%
“…Furthermore, a study in Mexico found that diabetes is the main associated comorbidity.7 In our study, diabetes was present in 27.8% of the patients, similar to other cohorts (20%, 30.4%, and 18%) [14][15][16] . Other associated factors have been studied: diet, smoking, alcohol consumption, fatigue, toxic exposure, and disability progression and quality of life [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of physical exercise are well documented in the literature, especially for PWD. Doneddu et al (2020) found that strength training reduces nerve lesions in patients with chronic in ammatory demyelinating polyradiculoneuropathy, due to muscle ber hypertrophy, the antiin ammatory effect of exercise or an increase in neural impulse.…”
Section: Introductionmentioning
confidence: 99%